2012
DOI: 10.1675/063.035.sp113
|View full text |Cite
|
Sign up to set email alerts
|

Winter and Summer Home Ranges and Core use Areas of Double-Crested Cormorants Captured near Aquaculture Facilities in the Southeastern United States

Abstract: Numbers of Double-crested Cormorants (Phalacrocorax auritus) wintering in the southeastern United States have increased dramatically during the last 30 years concomitant with the rise of the aquaculture industry in this region. These cormorants commonly foraged at commercial aquaculture facilities and thereby came into conflict with farmers. Various interest groups are seeking ecologically sound strategies for minimizing the effects of burgeoning cormorant populations. Therefore, this study was conducted to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…The team's marked birds generally had larger winter home ranges than summer home ranges, similar to results of Scherr et al (2010) and differing from results of King et al (2012a). The team found birds from Baker's Lake having nearly double winter home range sizes than summer home ranges, while birds from the TNC Preserve had slightly larger winter home ranges than during the summer.…”
Section: Other Seasonal and Demographic Information About Cormorantssupporting
confidence: 53%
See 2 more Smart Citations
“…The team's marked birds generally had larger winter home ranges than summer home ranges, similar to results of Scherr et al (2010) and differing from results of King et al (2012a). The team found birds from Baker's Lake having nearly double winter home range sizes than summer home ranges, while birds from the TNC Preserve had slightly larger winter home ranges than during the summer.…”
Section: Other Seasonal and Demographic Information About Cormorantssupporting
confidence: 53%
“…In general, among the piscivorous birds detected in the Chicago area, the Double-Crested Cormorant is the species most likely to act as a potential vector of Asian carp DNA in the CAWS. Several reasons for this view include: (1) cormorants are aggressive and opportunistic predators of fish (Dorr et al 2014); (2) cormorants are the most common piscivorous species during the breeding season in the Chicago area (see Table 1); (3) they often make long flights (>30 km) daily , King et al 2012a, increasing the likelihood that they could forage in invasive carp-infested waters and return to the breeding colony; (4) cormorants are well-known for producing large quantities of fecal material in and around nesting colonies; (5) viable carp DNA have been found in cormorant fecal material (ACRCC 2013(ACRCC , 2014Merkes et al 2014); and (6) populations within the Chicago area have invasive carp DNA present in throat and cloacal swabs (Guilfoyle et al 2017). In addition, all other piscivorous birds breeding in the Chicago area have much lower population counts based on the eBird data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we restricted analysis to only those California Gulls with ≥ 20 locations per season. This sample size was similar to that selected by King et al (2012), but we recognize that this analysis is still vulnerable to the influence of small sample size. Therefore, we used the estimated home range and core use area sizes to compare relative spatial use among seasons and did not focus on the absolute size of individual home ranges in our interpretation.…”
Section: Statistical Analysis Of Tracking Datamentioning
confidence: 99%
“…With increased aquaculture, researchers suggest cormorants have shifted their winter range from the Gulf of Mexico coast to encompass these areas of high catfish production (Glahn and Stickley 1995;King et al 2010). Satellite telemetry data revealed the summer ranges of cormorants captured near southeastern aquacul-ture facilities include the Great Lakes and the Prairie Pothole Region of the Northern Great Plains (King et al 2012). Moreover, King et al (2010) reported a 454% increase in band recoveries from southeastern aquaculture areas compared to a 55% increase in other areas since the mid-1980s.…”
mentioning
confidence: 99%